FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Calvin Wiratama; Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2026)
The purpose of this study is to obtain empirical evidence regarding the factors that influence firm value which include profitability, leverage, company size, with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses secondary data. This research was conducted with a sample of 35 manufacturing companies with the technique used in this research is purposive sampling. Data processing in this study used the SPSS 28 program. The results obtained from this study indicate that profitability has a positive effect on firm value, while leverage, firm size, and dividend policy do not have a positive effect on firm value. The results also show that dividend policy does not moderate the effect of profitability and leverage on firm value.